The Trend of Linguistic Studies on Social Media in Indonesian Linguistic Journals - Harahap, Ahmad Fadli; Rizky Vita Losi; Hanna Maria Panggabean; Ronika Apriyanti Manik; Roobby Hamdanur; Tahan HJ Sihombing; Sahat Maringan Samosir (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The focus of linguistic research has been shift in the past five years from face to face communication to online communication. This research employed content analysis on a number of articles that had been published in linguistics journals across Indonesia since 2020 to 2024, with linguistic aspect in social media as the main focus of the research. This current research has revealed that in the past five years, the number of publications used social media as their data source had improved. Among those publications, the most dominant research designed was qualitative descriptive. In addition, content analysis is the most dominant method to analyze the data. Instagram is the most frequently platform used as data resources in linguistic research. Researchers are particularly interested to investigate pragmatic aspects towards the online communication in social media. Based on the findings, future research is encouraged to use more diverse research designs, expand the scope of linguistic domains, and explore new platforms such as threads to better capture evolving digital language trends. Researchers are also advised to continuously adapt their methods and analyses to the dynamic nature of online communication in Indonesia.